Substitusi Tepung Terigu dengan Tepung Pati ubi Jalar (Ipomoea batatas L.) pada Pembuatan Mi kering - Akhyar Ali; Dewi Fortuna Ayu (Universitas Riau, 2009)
The objective of this research was to find the optimum substitution of wheat flour with sweet potato starch flour (Ipomoea batatas L.) in making noodle. The research was arranged in Completely Randomized Design with three replications. The treatments were PO (100% wheat flour); P1 (10% sweet potato starch flour and 90% wheat flour); P2 (20% sweet potato starch flour and 80% wheat flour); P3 (30% sweet potato starch flour and 70% wheat flour); and P4 (40% sweet potato starch flour and 60% wheat flour). The result indicated that treatments did not significantly influence water content, ash content, proteinscontent, starch content, and elasticity but significantly influenced flavor and taste of fried noodle. All the treatments met the SII for dried noodle (SII 0178-90). The best treatment was P2 (20% sweet potato starch flour and 80% wheat flour) for all parameters.